Sistem Informasi Pengolahan Data Keuangan Berbasis Web pada CV Hanling Batam - Sahara Sahara; Leni Lestari (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
CV Hanling is a company engaged in the wood furniture industry and furniture retail trade. In the processing of financial data CV Hanling still uses Microsoft Office Excel so often there are errors in data processing resulting in easily lost and deleted files. In the process of making the report still takes a long time because it is not supported by the information system. With these problems, it takes an information system that is able to overcome the problems that exist in CV Hanling. The purpose of this study is to create a web-based financial data processing information system, by processing financial data in a systems will produce a report recording financial data systems. The results of this study are financial data processing information systems that are made to provide convenience in the process of processing financial data ranging from recording transactions to the presentation of financial statements on CV Hanling. For data storage media already stored in the database, thus speeding up the search for data.